An investigation into ict pedagogical application among efl pre-service teachers of ud-ufls during their teaching practicum at high schools - Dinh Ngoc Thu (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
The integration of educational technology, particularly Information and Communication technology (ICT), is crucial in 21st-century foreign language classrooms. However, most of the previous research overlooked student engagement as a factor when assessing the ICT adoption of the teachers. Therefore, drawing upon the PICRAT model, which underscores both student interaction with technology and teacher ICT adoption, the research aims to analyze UD-UFLS EFL pre-service teachers’ use of ICT and student interaction with such technology during their teaching practicum in teaching English at some high schools in Danang, Vietnam, based on PICRAT model. The study utilised questionnaires with 28 EFL pre-service teachers from the University of Danang – University of Foreign Language Studies, followed by interviews with selected groups of pre-service teachers participants and the analysis of documentation, including 67 lesson plans, to gather both quantitative and qualitative data. The findings revealed that most teachers' ICT adoption predominantly fell within the "Replaces" and “Amplifies” level, indicating a substitution of traditional teaching methods and improvement in student learning with ICT tools. Student interaction tended to be passive, with interactive and creative engagements being less common. Various barriers such as limited ICT resources and time constraints hindered ICT adoption, suggesting avenues for enhancing its integration into teaching and learning processes, such as regular updates on ICT infrastructure, more funds for ICT facilities, high-speed internet connection and technical staff.